Revisiting the leading role of the Roman upper classes in slavery or slavery conditions (2018)
The ancient Roman society was not duplicitous about its socioeconomic dependence upon slaves. This paper, while presenting the developments that brought about slavery or slave conditions during the late Republic and at the beginning of the Roman Empire, dwells on the role of the Roman upper classes in making slaves constant features of Roman agriculture, industry, domestic life, entertainment and virtually all other facets of Roman life. The paper illustrates the upper classes' taste for slavery and their principal part as the promoters of the institution with Plutarch's reference to the Roman statesman, Cato, in Plutarch's Parallel Lives. With the active and preponderant role of the wealthy and influential Romans' use of slaves to function and maintain their political, social, and economic life at this time, the paper notes that Rome's historical pre-eminence would be non- existent without slaves. Therefore, it is concluded that the record of the Roman upper classes in creating slavery conditions and in entrenching slavery suggests that a successful fight against slavery in any form could only mean a deliberate fight against the rich and the powerful or breaking free from the yoke of the oppressors whose desire for slaves is unending. A study on Roman stories of manumission would be a good follow up to this work.